Incidence and risk of rash to mTOR inhibitors in cancer patients – a meta-analysis of randomized controlled trials. (January 2015) - Shameem, Raji; Lacouture, Mario; Wu, Shenhong
Abstract Background. Inhibitors of the mammalian target of rapamycin (mTOR) are currently approved for the treatment of several cancers, and their use is associated with serious rash, which affects patient's quality of life and leads to undesirable dose reductions or interruptions. A meta-analysis of randomized controlled trials (RCTs) was performed to determine the overall risk of developing high-grade rash with mTOR inhibitors in cancer patients. Methods. We searched the PubMed database and abstracts presented at the American Society of Clinical Oncology (ASCO) meetings up to December 2013 for relevant studies. Eligible studies included RCTs in which everolimus or temsirolimus was compared to controls in cancer patients. The summary incidence, relative risk (RR), and 95% confidence intervals (CI) were calculated using a random- or fixed-effects model depending on the heterogeneity of the included trials. Results. A total of 11 RCTs with 4752 patients (mTORs: 2725, controls: 2027) with a variety of solid tumors were included in the analysis. The incidences of all-grade (grade 1–4) and high-grade rash (grade 3–4) were 27.3% (95% CI 21.0–34.7%) and 1.0% (95% CI 0.6–1.4%), respectively. In comparison with controls, mTOR inhibitors significantly increased the risk for developing all-grade rash (RR = 3.55, 95% CI 3.0–4.20, p < 0.001) and high-grade rash (RR = 4.25, 95% CI 1.63–11.10, p = 0.003). The increased risk of high-grade rash did not vary significantly among different tumors (p = 0.91). There was no significant difference between everolimus and temsirolimus (p = 0.60). There was also no significant difference between mTOR inhibitors alone and in combination with other agents (p = 0.57). Conclusions. Everolimus and temsirolimus significantly increased the risk of high-grade rash in cancer patients. Early recognition and appropriate treatment is recommended.